A Medication Reminders and Disposal Mobile Application Using Data Encryption Technique - Foong, Clement Wen Kai; Ramli, Sofia Najwa (Applied Information Technology And Computer Science, 2025)
Medication non-adherence and improper disposal pose significant challenges to society and environment particularly in Malaysia. Therefore, mobile application MediCare+ has been introduced to address these issues by combining medication reminders, disposal guidance, and an Artificial Intelligence (AI) chatbot into a single, user-friendly platform. While current applications primarily focus on medication reminders, MediCare+ provides a comprehensive solution with personalized assistance and proper disposal information. Developed using Flutter and Firebase, the application’s core innovation is an AI agent powered by the Gemini API with function calling. This allows it to perform advanced tasks like searching trusted medical sources and locating nearby disposal sites. MediCare+ also provides AES-256-CBC encryption for sensitive medicine data. A prototyping methodology was used to develop the application. MediCare+ was developed primarily emphasis on Android. The development of MediCare+ will assist patients with adherence to their prescriptions and greatly reduce the pollution caused by improper disposal of medicines.